Exploring the organizational resilience and sustainability of the service related industries during and after covid-19 pandemic - Pathma Devi, Veerasingam (2023)
The COVID-19 pandemic has significantly impacted service-related industries worldwide, leading to the adoption of new strategies and procedures to ensure organizational resilience and sustainability. This research project aims to explore the organizational resilience and sustainability of service-related industries during and after the pandemic. The qualitative method approach using face to face interview with semi-structured questionnaire is used in this study. The study explores the impact of Covid-19 on overall business operation, interrogate the strategies adopted by each service sectors for sustain in the market, study the lesson learnt and preparedness of SME‟s to face another global crisis or pandemic. The study concludes that service-related industries can enhance their organizational resilience and sustainability by adopting a proactive and adaptive approach, leveraging technology, developing effective communication channels, developing customer relationship, supply chain resilience, transformation in organizational culture, strong leadership, financial contingency planning and interference of good government policy that support the SME‟s to sustain during the pandemic. The research findings provide insights that can guide organizations in enhancing their resilience and sustainability in the face of future crises. This study contributes to the existing literature on organizational resilience and sustainability and highlights the importance of developing a comprehensive approach to crisis management in service-related industries.